Sosialisasi Gizi Makanan Sehat dan Seimbang Asal Protein Hewani untuk Mencegah Stunting - Andri; Permadi, Edy; Lestari, Retno Budi (DHARMA RAFLESIA, 2024)
Stunting is a condition where the body experiences a lack of nutritional intake and does not meet nutritional needs over a long period. Kubu Raya Regency has several areas that still need to be studied, such as healthy and balanced food from animal protein. This community service aims to increase knowledge and awareness of consuming a balanced diet derived from animal protein to prevent stunting. Socialization was carried out in Rasau Jaya II Village, Rasau Jaya District. The method used in community service is education about sources and types of nutritious and balanced food from animal protein and strategies for providing healthy food from animal protein at home. The result of community service is that the people of Rasau Jaya II Village better understand the benefits of animal protein to prevent stunting and increase the consumption of nutritious and balanced food from animal protein. Socialization of food and balanced nutrition from animal protein needs to be carried out more widely to educate the public in areas that still have the potential for stunting